New taxonomic treatment for Trichomanes parvulum Poir. and T. dregei Bosch (Hymenophyllaceae, Polypodiidae) - Dubuisson, Jean-Yves; Nivart, Adele; Senterre, Bruno; Rouhan, Germinal (Phytotaxa, 2021)
N/A